Preparation method and application of cross-linked carboxymethyl cellulose material
By using nanocellulose as crosslinking agents, the crosslinking mercaptocellulose material is prepared, and the problem of impurity residue in the prior art is solved, the biosafety and water absorption of the material are improved, and the drug disintegration effect and safety are enhanced.
Patent Information
- Application Number
- CN202311822997.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-06-27
Smart Images

Figure CN120209363A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of natural polymers and pharmaceutical excipients, and particularly relates to a preparation method and application of a cross-linked carboxymethyl cellulose material. Background Art
[0002] Sodium carboxymethyl cellulose cross-linked has hygroscopicity and hydrophilicity but is insoluble in water. Sodium carboxymethyl cellulose cross-linked can absorb several times its own weight of water in water and swell rapidly. Therefore, as a pharmaceutical excipient, sodium carboxymethyl cellulose cross-linked has advantages such as good disintegration effect, fast speed, and wide application range, and is known as a "super disintegrant".
[0003] The reported methods for preparing sodium carboxymethyl cellulose cross-linked mainly include the sulfuric acid catalysis method and the cross-linking agent method. The sulfuric acid catalysis method requires the use of sulfuric acid with a high concentration as a catalyst, and the cross-linking agent method requires the use of glutaraldehyde, etc. as a cross-linking agent. A large amount of sulfuric acid or glutaraldehyde will remain in the prepared product, and sufficient washing is required before use. The washing process will not only generate a large amount of waste liquid; moreover, even if a large amount of solvent is used for washing, it is still impossible to avoid the problem of a relatively high content of residual impurities in the product. When using sodium carboxymethyl cellulose cross-linked with a relatively high content of impurities as an excipient to prepare drugs, it will not only affect the drug efficacy, but also pose a safety hazard. Summary of the Invention
[0004] In order to improve the deficiencies of the prior art, the present invention provides a preparation method and application of a cross-linked carboxymethyl cellulose material, using nanocellulose as a cross-linking agent, and the obtained product has high biosafety.
[0005] In a first aspect, the present invention provides a preparation method of a cross-linked carboxymethyl cellulose material, and the preparation method includes the following steps:
[0006] By mass, mix 2-10 parts of sodium carboxymethyl cellulose, 0.003-0.1 part of nanocellulose, 0.001-0.1 part of an acid substance with an aqueous solution, react at a temperature of 0-80 °C for 1-2 h, and then dry to obtain a cross-linked carboxymethyl cellulose material.
[0007] According to an embodiment of the present invention, the pH value of the mixed solution is 1.0-6.5, and preferably the pH value of the mixed solution is 2.0-5.0.
[0008] According to an embodiment of the present invention, the drying includes the following steps: drying the reaction product at a temperature of 80-160 °C for 1-6 h, and preferably drying the reaction product at a temperature of 100-140 °C for 2-4 h.
[0009] According to an embodiment of the present invention, the degree of substitution of the sodium carboxymethyl cellulose is 0.50 to 1.00, preferably the degree of substitution of the sodium carboxymethyl cellulose is 0.60 to 0.85, for example 0.55, 0.65, 0.75, 0.85, 0.95.
[0010] According to an embodiment of the present invention, the nanocellulose is selected from at least one of cellulose nanocrystals, cellulose microfibrils, and bacterial nanofibers.
[0011] According to an embodiment of the present invention, the acid substance is selected from at least one of phosphoric acid, hydrochloric acid, sulfuric acid, malic acid, citric acid, tartaric acid, succinic acid, fumaric acid, maleic acid, edetic acid, adipic acid, oxalic acid, diethylenetriaminepentaacetic acid, polyphosphoric acid, diethylenetriamine penta(methylphosphonic acid), nitric acid, sodium hydrogen phosphate, sodium dihydrogen phosphate, potassium hydrogen phosphate, potassium dihydrogen phosphate, lactic acid, acetic acid, formic acid, propionic acid, monochloroacetic acid, trichloroacetic acid, for example citric acid.
[0012] According to an embodiment of the present invention, mixing 2 to 10 parts of sodium carboxymethyl cellulose, 0.003 to 0.1 part of nanocellulose, 0.001 to 0.1 part of acid substance with an aqueous solution includes the following steps:
[0013] a. Mix 2 to 10 parts of sodium carboxymethyl cellulose with an alcohol solution to obtain a sodium carboxymethyl cellulose / alcohol dispersion;
[0014] b. Mix 1 to 3 parts of nanocellulose, 0.5 to 4 parts of acid substance with an aqueous solution to obtain a mixed solution;
[0015] c. Add the mixed solution to the sodium carboxymethyl cellulose / alcohol dispersion.
[0016] According to an embodiment of the present invention, the alcohol in step a is selected from at least one of ethanol, methanol, and isopropanol.
[0017] According to an embodiment of the present invention, in the sodium carboxymethyl cellulose / alcohol solution, the mass concentration of sodium carboxymethyl cellulose is 20% to 50%, preferably the mass concentration of sodium carboxymethyl cellulose is 30% to 40%.
[0018] According to an embodiment of the present invention, in the mixed solution, the mass concentration of the nanocellulose is 0.1% to 1.0%, preferably the mass concentration of the nanocellulose is 0.3% to 0.7%.
[0019] According to an embodiment of the present invention, in the mixed solution, the mass concentration of the acid substance is 0.1% to 3.0%, preferably the mass concentration of the acid substance is 0.5% to 2.0%, for example 0.2%, 0.8%, 1.2%, 1.5%, 1.8%, 2.3%, 2.8%.
[0020] According to an embodiment of the present invention, the mass ratio of the sodium carboxymethyl cellulose / alcohol dispersion to the mixed solution is 1:1 to 10:1, and preferably the mass ratio of the sodium carboxymethyl cellulose / alcohol solution to the mixture is 3:1 to 6:1.
[0021] In a second aspect, the present invention also provides a crosslinked carboxymethyl cellulose prepared by the above method. The water absorption ratio of the crosslinked carboxymethyl cellulose powder is 1500% to 10000%, preferably the water absorption ratio of the crosslinked carboxymethyl cellulose powder is 2000% to 6000%, and further preferably, the water absorption ratio of the crosslinked carboxymethyl cellulose powder is 3000% to 5000%.
[0022] According to an embodiment of the present invention, the crosslinked carboxymethyl cellulose is in a powder structure.
[0023] According to an embodiment of the present invention, the crosslinked carboxymethyl cellulose powder has a fibrous structure with a diameter of 10 nm to 100 nm. Preferably, the highly water-absorbent crosslinked carboxymethyl cellulose powder has a fibrous structure with a diameter of 20 nm to 60 nm, such as 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm.
[0024] According to an embodiment of the present invention, the crosslinked carboxymethyl cellulose material has a basic infrared spectrum as shown in Figure 2 , Figure 6 or Figure 10 .
[0025] According to an embodiment of the present invention, the crosslinked carboxymethyl cellulose material has a basic scanning electron microscope photograph as shown in Figure 3 , Figure 7 or Figure 11 .
[0026] According to an embodiment of the present invention, the crosslinked carboxymethyl cellulose material has a basic scanning electron microscope photograph as shown in Figure 4 , Figure 8 or Figure 12 .
[0027] In a third aspect, the present invention provides an application of the above crosslinked carboxymethyl cellulose material in a filler, such as used as a disintegrant. The crosslinked carboxymethyl cellulose powder can be used as a disintegrant to promote the rapid release of drugs.
[0028] In a fourth aspect, the present invention provides a drug, which includes an effective amount of a medicament and a disintegrant, and the disintegrant includes the crosslinked carboxymethyl cellulose material as described above.
[0029] Beneficial effects
[0030] The present invention uses nanocellulose as a crosslinking agent to prepare superabsorbent sodium carboxymethyl cellulose. In the present invention, the hydroxyl groups in the crosslinking agent nanocellulose react with the carboxyl groups in sodium carboxymethyl cellulose. At the same time, there are also a large number of hydrogen bond interactions between nanocellulose and sodium carboxymethyl cellulose. Therefore, the obtained sodium carboxymethyl cellulose will not migrate or be lost, and the resulting product has high biological safety and important practical value.
[0031] The water absorption ratio of the sodium carboxymethyl cellulose prepared in the present invention is 1500% - 10000%, showing extremely high water absorption. Description of the Drawings
[0032] Figure 1 It is a transmission electron microscope photograph of the cellulose nanocrystals in Example 1.
[0033] Figure 2 It is an infrared spectrum of the crosslinked sodium carboxymethyl cellulose powder in Example 1.
[0034] Figure 3 It is a scanning electron microscope photograph of the crosslinked sodium carboxymethyl cellulose powder in Example 1.
[0035] Figure 4 It is a water absorption photograph of the crosslinked sodium carboxymethyl cellulose powder in Example 1.
[0036] Figure 5 It is an atomic force microscope photograph of the cellulose nanocrystals in Example 2.
[0037] Figure 6 It is an infrared spectrum of the crosslinked sodium carboxymethyl cellulose powder in Example 2.
[0038] Figure 7 It is a scanning electron microscope photograph of the crosslinked sodium carboxymethyl cellulose powder in Example 2.
[0039] Figure 8 It is a water absorption photograph of the crosslinked sodium carboxymethyl cellulose powder in Example 2.
[0040] Figure 9 It is a transmission electron microscope photograph of the cellulose nanocrystals in Example 3.
[0041] Figure 10 It is an infrared spectrum of the crosslinked sodium carboxymethyl cellulose powder in Example 3.
[0042] Figure 11 It is a scanning electron microscope photograph of the cellulose nanofibers in Example 4.
[0043] Figure 12 It is a water absorption photograph of the crosslinked sodium carboxymethyl cellulose powder in Example 4. Detailed Embodiments
[0044] The preparation method and application of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only illustrative explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0045] Unless otherwise specified, the raw materials and reagents used in the following embodiments are all commercially available products or can be prepared by known methods.
[0046] Example 1
[0047] The preparation of crosslinked carboxymethyl cellulose includes the following steps:
[0048] (1) In 20 g of sodium carboxymethyl cellulose (substitution degree 0.65) / ethanol solution (wherein, 5 g of sodium carboxymethyl cellulose and 15 g of ethanol), 1 g of cellulose nanocrystals / citric acid / aqueous solution (cellulose nanocrystal concentration 0.8 wt%, citric acid concentration 0.8 wt%) is added, and stirred at 25 °C for 2 h to obtain a reaction solution.
[0049] (2) The reaction solution is dried at 130 °C for 4 h to obtain crosslinked carboxymethyl cellulose.
[0050] The cellulose nanocrystals used are prepared by the sulfuric acid method, and the preparation method refers to the literature Cellulose, 2006, 13, 171 - 180; it is a rod-shaped nanomaterial with a diameter of 20 - 50 nm, as Figure 1 shown.
[0051] See Figure 2 shown, which is the infrared spectrum of the crosslinked carboxymethyl cellulose powder prepared in this example. As can be seen from the figure, the hydroxyl O - H stretching vibration peak of the crosslinked carboxymethyl cellulose prepared in this example is at 3300 cm -1 , the COONa stretching vibration peak is at 1587 cm -1 and the C - O - C stretching vibration peak is at 1018 cm -1 .
[0052] See Figure 3 shown, which is the scanning electron microscope photograph of the crosslinked carboxymethyl cellulose prepared in this example. As can be seen from the figure, the crosslinked carboxymethyl cellulose prepared in this example is a fibrous solid material with a diameter of 20 μm.
[0053] As Figure 4As shown, 0.6 g of the cross-linked carboxymethyl cellulose powder prepared in this example was placed in 50 mL of water. The cross-linked carboxymethyl cellulose powder could absorb water up to 15 mL. Thus, it can be seen that the water absorption ratio of the cross-linked carboxymethyl cellulose powder in this example was 2500%, indicating that the powder of the present invention had a remarkable water absorption effect.
[0054] Test Example 1
[0055] The cross-linked carboxymethyl cellulose obtained in Example 1 was compared with commercially available cross-linked carboxymethyl cellulose (from FMC Corporation) in terms of drug release rate. The specific operation was as follows: 2 g of the cross-linked carboxymethyl cellulose prepared in Example 1 (or 2 g of commercially available cross-linked carboxymethyl cellulose), 46 g of microcrystalline cellulose, 46 g of glucose, 1 g of silicon dioxide, 5 g of polyvinylpyrrolidone, 1 g of magnesium stearate, and 1 g of lake were stirred and mixed; tablets were prepared by tableting method, with a tablet weight of 0.6 g and a tableting pressure of 80 kN.
[0056] The disintegration experiment was tested on a disintegrator. The disintegration medium was hydrochloric acid aqueous solution with pH = 1.0 (simulating gastric juice), and the temperature was 37.5 °C. Six parallel experiments were carried out for each sample. The disintegration time of the tablets was as shown in the following table:
[0057] Table 1 Disintegration Time of Drugs
[0058] 1 2 3 4 5 6 Commercial crosslinked carboxymethyl cellulose 24’30” 23’40” 24’00” 24’10” 22’15” 28’25” Crosslinked carboxymethyl cellulose of Example 1 14’55” 15’10” 17’10” 15’55” 16’30” 16’45”
[0059] As can be seen from Table 1, the cross-linked carboxymethyl cellulose prepared in Example 1 had a faster disintegration rate than the commercially available cross-linked carboxymethyl cellulose.
[0060] Example 2
[0061] The preparation of the cross-linked carboxymethyl cellulose material included the following steps:
[0062] (1) In 30 g of sodium carboxymethyl cellulose (substitution degree 0.75) / ethanol solution (wherein, 10 g of sodium carboxymethyl cellulose and 20 g of ethanol), 1 g of cellulose nanocrystals / succinic acid / aqueous solution (cellulose nanocrystal concentration 1.0 wt%, succinic acid concentration 0.8 wt%) was added, and it was stirred at 25 °C for 2 h to obtain a reaction solution.
[0063] (2) The reaction solution was dried at 150 °C for 4 h to obtain cross-linked carboxymethyl cellulose.
[0064] The cellulose nanocrystals used in this example were prepared by the sulfuric acid method, and the preparation method was referred to the literature Cellulose, 2006, 13, 171 - 180; it was a long rod-shaped nanomaterial with a diameter of 20 - 50 nm, as Figure 5 shown.
[0065] See Figure 6As shown, it is the infrared spectrum of the ground powder of the crosslinked carboxymethyl cellulose prepared in this example. The stretching vibration peak of the hydroxyl O-H is 3209 cm -1 , the stretching vibration peak of COONa is 1585 cm -1 and the stretching vibration peak of C-O-C is 1022 cm -1 .
[0066] See Figure 7 As shown, it is the SEM image of the crosslinked carboxymethyl cellulose prepared in this example. It can be seen from the figure that the crosslinked carboxymethyl cellulose is a fibrous solid material with a diameter of 20 μm.
[0067] See Figure 8 As shown, 1.0 g of the crosslinked carboxymethyl cellulose powder prepared in this example was placed in 50 mL of water, and it could absorb water up to 21 mL. Thus, it can be seen that the water absorption ratio of the crosslinked carboxymethyl cellulose prepared in this example is 2100%, showing high water absorbency.
[0068] Example 3
[0069] The preparation of the crosslinked carboxymethyl cellulose material includes the following steps:
[0070] (1) In 20 g of sodium carboxymethyl cellulose (substitution degree 0.70) / ethanol solution (wherein, 4 g of sodium carboxymethyl cellulose and 16 g of ethanol), 1 g of cellulose nanocrystals / hydrochloric acid / aqueous solution (cellulose nanocrystal concentration 0.5 wt%, hydrochloric acid concentration 0.2 wt%) was added, and it was stirred at 25 °C for 2 h to obtain a reaction solution.
[0071] (2) The reaction solution was dried at 140 °C for 4 h to obtain the crosslinked carboxymethyl cellulose material.
[0072] The cellulose nanocrystals used were prepared by the sulfuric acid method, and the preparation method was referred to the literature Cellulose, 2006, 13, 171 - 180; it is a long rod-shaped nanomaterial with a diameter of 20 - 50 nm, as Figure 9 shown.
[0073] See Figure 10 As shown, it is the infrared spectrum of the crosslinked carboxymethyl cellulose powder prepared in this example. The stretching vibration peak of the hydroxyl O-H is 3278 cm -1 , the stretching vibration peak of COONa is 1597 cm -1 and the stretching vibration peak of C-O-C is 1020 cm -1 .
[0074] The crosslinked carboxymethyl cellulose prepared in this example is a fibrous solid material with a diameter of 20 μm.
[0075] Put 1.0 g of the cross-linked carboxymethyl cellulose powder prepared in this example into 50 mL of water. It can absorb water up to 25 mL, and the water absorption ratio is 2500%. This indicates that the cross-linked carboxymethyl cellulose powder prepared in this example has a significant water absorption effect.
[0076] Test Example 2
[0077] Compare the drug release rates of the cross-linked carboxymethyl cellulose obtained in Example 3 and the commercial cross-linked carboxymethyl cellulose (FMC Corporation). Specific operation: 1 g of cross-linked carboxymethyl cellulose, 46 g of microcrystalline cellulose, 46 g of glucose, 2 g of silicon dioxide, 5 g of polyvinylpyrrolidone, 1 g of magnesium stearate, and 1 g of lake pigment were stirred and mixed; tablets were prepared by tableting method, with a tablet weight of 0.6 g and a tableting pressure of 80 kN.
[0078] The disintegration experiment was tested on a disintegrator. The disintegration medium was hydrochloric acid aqueous solution with pH = 1.0 (simulating gastric juice), and the temperature was 37.5 °C. 6 parallel experiments were carried out for each sample. The tablet disintegration times are shown in Table 2:
[0079] Table 2 Tablet Disintegration Times
[0080] 1 2 3 4 5 6 Commercial crosslinked carboxymethyl cellulose 32’60” 32’10” 32’00” 33’10” 32’30” 33’20” Crosslinked carboxymethyl cellulose of Example 3 26’40” 27’25” 27’00” 26’50” 27’30” 26’55”
[0081] It can be seen from the above results that the cross-linked carboxymethyl cellulose in Example 3 has a faster disintegration rate than the commercial cross-linked carboxymethyl cellulose.
[0082] Example 4
[0083] The preparation of the cross-linked carboxymethyl cellulose material includes the following steps:
[0084] (1) Add 1 g of cellulose nanofiber / malic acid / aqueous solution (cellulose nanofiber concentration 0.5 wt%, malic acid concentration 0.5 wt%) to 18 g of sodium carboxymethyl cellulose (substitution degree 0.70) / ethanol solution (wherein, 3 g of sodium carboxymethyl cellulose and 15 g of ethanol), and stir and react at 25 °C for 2 h to obtain a reaction solution.
[0085] (2) Dry the reaction solution at 150 °C for 5 h to obtain the cross-linked carboxymethyl cellulose material.
[0086] The cellulose nanofibers used were prepared by the 2,2’,6,6’-tetramethylpiperidine-1-oxyl (TEMPO) method. The preparation method refers to the literature Biomacromolecules, 2007, 8, 2485 - 2491; it is a fibrous material with a diameter of 30 - 40 nm, as Figure 11 shown.
[0087] See Figure 12As shown, 1.0 g of the cross-linked carboxymethyl cellulose powder prepared in this example was placed in 50 mL of water, and it could absorb water up to 20 mL, with a water absorption ratio of 2000%, indicating that the powder of the present invention has a significant water absorption effect.
[0088] Example 5
[0089] Preparation of the cross-linked carboxymethyl cellulose material includes the following steps:
[0090] (1) In 26 g of sodium carboxymethyl cellulose (substitution degree 0.70) / ethanol solution (wherein, 6 g of sodium carboxymethyl cellulose and 20 g of ethanol), 1 g of cellulose nanofiber / oxalic acid / aqueous solution (cellulose nanocrystal concentration 1.0 wt%, oxalic acid concentration 0.6 wt%) was added, and the mixture was stirred and reacted at 25 °C for 2 h to obtain a reaction solution.
[0091] (2) The reaction solution was dried at 130 °C for 5 h to obtain the cross-linked carboxymethyl cellulose material.
[0092] The cellulose nanofibers used were prepared by the 2,2’,6,6’-tetramethylpiperidine-1-oxyl (TEMPO) method, and the preparation method was referred to the literature Biomacromolecules, 2007, 8, 2485 - 2491; it was a fibrous material with a diameter of 30 - 40 nm.
[0093] The obtained cross-linked carboxymethyl cellulose powder was a fibrous solid material with a diameter of 20 μm.
[0094] 1.0 g of the cross-linked carboxymethyl cellulose powder prepared in this example was placed in 50 mL of water, and it could absorb water up to 35 mL, with a water absorption ratio of 3500%, indicating that the cross-linked carboxymethyl cellulose powder prepared in this example has a significant water absorption effect.
[0095] The specific embodiments of the present invention have been exemplarily described above through examples. However, the protection scope of the present invention is not limited to the above exemplary embodiments. Any modifications, equivalent replacements, improvements, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a crosslinked carboxymethyl cellulose material, characterized in that, The preparation method comprises the following steps: By mass, 2-10 parts of sodium carboxymethyl cellulose, 0.003-0.1 part of nanocellulose, 0.001-0.1 part of acid substance are mixed with an aqueous solution, reacted at a temperature of 0-80 °C for 1-2 h and then dried to obtain a crosslinked carboxymethyl cellulose material.
2. The preparation method of the cross-linked carboxymethyl cellulose material according to claim 1, characterized in that, The pH value of the mixed solution is 1.0-6.
5.
3. The preparation method of the crosslinked carboxymethyl cellulose material according to claim 1, characterized in that, The drying comprises the following steps: drying the reaction product at a temperature of 80-160 °C for 1-6 h.
4. The preparation method of the crosslinked carboxymethyl cellulose material according to claim 1, wherein The substitution degree of the sodium carboxymethyl cellulose is 0.50-1.
00.
5. The preparation method of the crosslinked carboxymethyl cellulose material according to claim 1, wherein, The nanocellulose is selected from at least one of cellulose nanocrystals, cellulose microfibrils, and bacterial nanofibers. Preferably, the acid substance is selected from at least one of phosphoric acid, hydrochloric acid, sulfuric acid, malic acid, citric acid, tartaric acid, succinic acid, fumaric acid, maleic acid, edetic acid, adipic acid, oxalic acid, diethylenetriaminepentaacetic acid, polyphosphoric acid, diethylenetriamine penta(methylphosphonic acid), nitric acid, sodium hydrogen phosphate, sodium dihydrogen phosphate, potassium hydrogen phosphate, potassium dihydrogen phosphate, lactic acid, acetic acid, formic acid, propionic acid, monochloroacetic acid, and trichloroacetic acid.
6. The preparation method of the crosslinked carboxymethyl cellulose material according to any one of claims 1-5, characterized in that, Mixing 2-10 parts of sodium carboxymethyl cellulose, 0.003-0.1 part of nanocellulose, 0.001-0.1 part of acid substance with an aqueous solution comprises the following steps: a. Mix 2-10 parts of sodium carboxymethyl cellulose with an alcohol solution to obtain a sodium carboxymethyl cellulose / alcohol dispersion; b. Mix 1-3 parts of nanocellulose, 0.5-4 parts of acid substance with an aqueous solution to obtain a mixed solution; c. Add the mixed solution to the sodium carboxymethyl cellulose / alcohol dispersion.
7. The preparation method of the crosslinked carboxymethyl cellulose material according to any one of claims 1-5, characterized in that, In the sodium carboxymethyl cellulose / alcohol solution, the mass concentration of sodium carboxymethyl cellulose is 20%-50%.
8. The preparation method of the cross-linked carboxymethyl cellulose material according to claim 6 or 7, characterized in that, In the mixed solution, the mass concentration of the nanocellulose is 0.1%-1.0%, and the mass concentration of the acid substance is 0.1%-3.0%. Preferably, the mass ratio of the sodium carboxymethyl cellulose / alcohol dispersion to the mixed solution is 1:1-10:
1.
9. A crosslinked carboxymethyl cellulose material prepared by the preparation method according to any one of claims 1-8, characterized in that, The water absorption ratio of the crosslinked carboxymethyl cellulose is 1500%-10000%. Preferably, the crosslinked carboxymethyl cellulose powder has a fibrous structure with a diameter of 10 nm-100 nm.
10. Application of the crosslinked carboxymethyl cellulose material prepared by the method according to any one of claims 1-8 or the crosslinked carboxymethyl cellulose material according to claim 8 in a filler, for example, used as a disintegrant. The crosslinked carboxymethyl cellulose powder can be used as a disintegrant to promote rapid release of a drug.
11. A drug, which comprises an effective amount of a medicament and a disintegrant, and the disintegrant comprises the crosslinked carboxymethyl cellulose material prepared by the method according to any one of claims 1-8 or the crosslinked carboxymethyl cellulose material according to claim 9.